PRODUCTION TECHNOLOGY OF LUNCH DISHES BASED ON VEGETABLES FOR SOCIAL NUTRITION - N. M. Stepanisheva; N. E. Posokina; O. YU. Lalina; A. P. Primak (Овощи России, 2015)
The seven-day recipe composition of lunch dishes for social nutrition of target groups of consumers was developed. The main components of this recipe are vegetables.